MENINGKATKAN KETERAMPILAN LINGUISTIK BAHASA INGGRIS MELALUI PROGRAM BILINGUAL DI SEKOLAH.docx - Ilham Soleh Khudin; Mikail Mega Maulana; Moh Darwis; Na'imah Na'imah (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2024)
This research aims to uncover schools' efforts in enhancing English language proficiency, revealing exemplary programs and their implications for students. The study utilizes a descriptive qualitative approach, employing data collection techniques such as observation, documentation, and in-depth interviews. Furthermore, data analysis techniques were applied from the beginning to the conclusion of the research. The research findings indicate that the school's efforts to enhance students' English language skills are evident within the school environment, manifested through announcements, school radio, instructions, and displays in various school areas entirely in English. Additionally, the school encourages its students to use English when acting as Masters of Ceremony. These school efforts are supported by exemplary programs such as using English-language math, science, and ICT textbooks, religious lectures, Hadith readings, ESL,